Research on Performance Optimization Algorithm of Resource and Environment Audit Based on Computer Technology - Wang, Yuhui (Computational intelligence and neuroscience, 2022)
With the rapid development of the economy and society, the sustainable development of resources and environment has been paid more and more attention. As an important part of the national environmental supervision system, resources and environmental audits have attracted great attention from the society. In order to explore the application effect of intelligent networking technology in resource and environment audit, this study carries out monitoring sampling, information collection, and later data processing optimization in resource and environment audit projects through the reference of artificial intelligence technology and method and combined with Internet of things big data analysis, which brings new Turks to the development of natural resource and environment audit and helps to improve the efficiency of audit work. Through the application of new technology in the sampling process of environmental information, the staff use new technology to collect, analyze, and mine data and explore how the new technology can promote the efficiency of resource and environmental audit and better promote the construction of ecological civilization.